Analisis Regresi Linear Berganda Pendugaan Bobot Hidup Sapi Bali Jantan Berdasarkan Ukuran Morfometrik - Theodorus Banu; Eva Binsasi; Fried Markus Allung Blegur; Alfred Nubatonis (Journal of Mathematics Theory and Applications, 2022)
Knowing the live weight of male Bali cattle is very important to increase the selling price. Meanwhile, the limited ownership of animal scales as a measuring device for live weight means that livestock farmers in remote areas do not maximize the selling price according to government regulations. This study aims to determine the factors that influence the live weight of male Bali cattle and to form the best estimator model through its morphometric measurements. A total of 51 male Bali cattle (2 to 3.5 years old) were used in this study. The results of the study were analyzed and mathematically met the requirements for finding factors that affect live weight morphometrically and forming the best estimating model using the linear regression method. The results of the regression analysis showed that chest circumference (X3), body length (X1) and body height (X2) respectively were factors that greatly influenced the live weight (Y=-255.161+1.253X1+2.148X3+0.033) of male Bali cattle with a coefficient of determination 97.8%, 97% and 96%. The best estimator model for male Bali cattle live weight uses 2 estimating variables, namely body length and chest circumference, namely. This model has a very significant effect ( with a coefficient of determination of 97.9%.